Determination of Child Origins in a Siri Marriage: Perspectives of Islamic Law and Positive Law in Indonesia - Fitri, Abd. Basit Misbachul (VRISPRAAK : International Journal of Law, 2025)
Siri marriage is a form of marriage that is religiously valid, but not registered at the Office of Religious Affairs (KUA), so it does not have legal force in state administration. One of the main problems caused by siri marriage is the legal status of children born from the marriage. Children born from a siri marriage often have no civil rights against their father, either in terms of inheritance or recording the father's name in the birth certificate. Based on Law Number 1 Year 1974 on Marriage and the Compilation of Islamic Law (KHI), children born from unregistered marriages only have a civil relationship with their mother. This study aims to analyse the legal provisions regarding the determination of the origin of children in a siri marriage and its implications for children's rights. The method used is a normative juridical approach by analysing the applicable regulations in Indonesia. The results show that although siri marriages are legal according to religion, children born from these marriages face limited legal rights. Therefore, isbat nikah is a legal alternative that can provide legal certainty for the status of children.